Análisis comparativo de eficiencia y precisión en levantamientos topográficos planialtimétricos con teodolito, estación total y RTK - Cadena Coello, Dagmar Adriana (2024)
A comparative analysis of the efficiency and precision in planialtimetric topographic surveys was carried out using theodolite, total station and RTK. The research reveals that the total station offers the best precision in measuring distances, the RTK stands out for its speed and efficiency in field time, and the theodolite is superior in measuring angles, although its use is longer and does not measures distances directly. The following differences in the measured areas were identified: a reduction of 3738.93 m² between the theodolite and the total station, and an increase of 394.228 m² between the total station and the RTK. These results highlight the higher accuracy of RTK and the high efficiency of the total station compared to the theodolite. It is recommended to consider the most appropriate technology according to the size and requirements of the project: the theodolite for small projects with limited budget, the total station for medium projects, and the RTK for large projects that require high precision. It is essential to invest in continuous training for staff and carefully evaluate the cost-benefit of each piece of equipment. Additionally, the gradual implementation of new technologies and a regular maintenance program are key to maximizing efficiency and accuracy in topographic surveys. This balanced strategy ensures optimal results adapted to the specific needs of each project.